Performance Study and Development of a 5-Axis C.N. C. Machine - Kumar M.; Baitha R.; Kumar S.; Kaushal R. (My University, 2025)
Using the conceptual design method, a Five-axis C.N.C. machine has been developed using the already available C.N.C. setup (R.P. setup). The C.N.C. machine setup has got mechatronic controls and a computer interface through CAMSOFT for various C.N.C. operations. The present work highlights the importance of conceptual design and innovation's role in developing C.N.C. machines. The work initially begins with studying an existing partially developed 3-axis C.N.C. setup with certain significant flaws. Conceptual design is applied to correct the existing problems and fabricate new components for the Five-axis C.N.C. milling machine. After getting feasible designs, the work moves into the fabrication stage, where all the corrective measures are taken, and specific new components are developed/ fabricated and added to the C.N.C. setup accordingly. The New milling attachments is developed successfully and installed on the C.N.C. machine setup. The working of the developed five-axis C.N.C. milling is tested by making 2D & 3D contoured products (three cases). It is found to be satisfactory based on various experiments (visual and dimensional inspection). © 2022 IEEE.